2020
DOI: 10.1111/cfs.12787
|View full text |Cite
|
Sign up to set email alerts
|

Parents' perceptions of a group‐based parenting programme in families with child protection and other family support services in a real‐life setting

Abstract: The aim of this study was to assess parents' satisfaction and perceived usefulness of the Incredible Years ® (IY ®) parenting programme in the Child Protection Services (CPS) context, where children's behaviour problems are common. Evidence-based programmes are rarely offered in CPS, and little is known about how they are perceived by parents. We compared parents (N = 62) with (N = 43) and without (N = 19) CPS contact regarding their satisfaction with the IY ® parenting programme, with information gathered fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Also, and contrary to expected, no significant effects of IY intervention were found on parenting stress and parental psychological well-being, a finding attributed to the fairly good initial levels of mental health in both the intervention and control groups, and the access of the parents in the control group to high-quality social and mental health services if needed. An additional study by the same authors reported that the parents from child protection services were committed and reasonably well engaged in the IY program, showing similar rates of attendance and satisfaction to non-referred parents (Karjalainen et al, 2020).…”
Section: R E S U M E Nmentioning
confidence: 92%
“…Also, and contrary to expected, no significant effects of IY intervention were found on parenting stress and parental psychological well-being, a finding attributed to the fairly good initial levels of mental health in both the intervention and control groups, and the access of the parents in the control group to high-quality social and mental health services if needed. An additional study by the same authors reported that the parents from child protection services were committed and reasonably well engaged in the IY program, showing similar rates of attendance and satisfaction to non-referred parents (Karjalainen et al, 2020).…”
Section: R E S U M E Nmentioning
confidence: 92%
“…For this reason, parents in the control condition received good care and services from health and social services and from their child-care facilities or school for their various problems during the study period. Also, some of the workers who attended to the families in the control group had received IY ® training, which suggests that they might have used these strategies with some parents in the control group, as was noticed in a survey carried out among Finnish IY Group Leaders [67]. The survey reported that 90% of the workers stated that their whole way of working changed after IY group leader training, becoming more empathic and client-focused, and they were able to support parenting more broadly and concretely.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…Viime aikoina joitakin alun perin muuhun käyttöympäristöön kehitettyjä näyttöön perustuvia menetelmiä on tutkittu myös lastensuojelun asiakasryhmällä hyvin tuloksin. Karjalaisen (2021) tutkimuksen mukaan Ihmeelliset vuodet -vanhemmuus ryhmän avulla voidaan onnistuneesti vähentää lasten käytös ongelmia lastensuojelun piirissä olevissa perheissä [46]. Tulosten mukaan lastensuojelussa asioivat vanhemmat myös sitoutuivat hyvin ohjelmaan ja pitivät sitä yhtä hyödyllisenä kuin vanhemmat, joilla ei ollut yhteyttä lastensuojeluun.…”
Section: Strategioita Lastensuojelun Tutkimusperustaisuuden Vahvistam...unclassified